Assessment of corruption in the humanitarian assistance in Puntland State of Somalia. Issue 1 (3rd February 2020) - Sofe, Abdinur Abdirisak
Abstract : Purpose: Corruption in humanitarian aid is one of the most worried and worst problems around the world. The existence of corruption acts in humanitarian aid delivery can endanger the already susceptible lives of the neediest individuals in the community. Amid serious humanitarian allegation in the country, this study aims to capture meaningful insights in humanitarian aid corruption in Puntland State of Somalia. Design/methodology/approach: The study applied qualitative method and used interview as a technique of data collection. The information obtained through the interview was analyzed by quoting and narration forms. Findings: The findings indicated numerous acts of corruption in all project stages including corruption in project granting and humanitarian staff employment, distortion of project targets and diversion of humanitarian project from targeted communities. The research also found that governmental and non-governmental actors are involved in the humanitarian corruption such as project managers and support staffs in addition to line ministries, parliament and community representatives. Research limitations/implications: Corruption is a taboo and is difficult to research; people do not want to share the information for fear of victimization. Concerned institutions were not willing to provide necessary materials which led to shortage of secondary data. Another problem encountered during the study has been that the humanitarian stakeholders (for instance, government, non-government and private institutions) acted reluctantly to cooperate because of suspicion that disclosing information may lead to negative effect on their business. To overcome the challenges, the study assured the confidentiality of the members and that information collected would be used for research purposes only. The study further combined various tools of data collection so that the weakness of one tool becomes the strength of the other; while the researcher made efforts to build rapport with the research participants. Originality/value: This study will contribute to the literature on corruption in the humanitarian aid. Specifically, the findings of this study will benefit academicians/researchers by giving empirical insights of corruption in the humanitarian aid in Puntland. It will benefit the government policymakers in the formulation of policies to combat corruption in the sector. Donors and aid agencies may also find the findings useful as they are key stakeholders who are interested in corruption in the humanitarian sector and finally the findings will benefit the wider society that is the primary victim of corruption in the humanitarian sector.